Tuneable Dual-Wavelength Erbium-Doped Fibre Laser Using Linear Cavity - Abdullah, Fairuz (2004)
The growth of optical communication system in recent years has been phenomenal. It is either in its applications, bandwidth offered, speed of data transferred or even the techniques used to achieve these. In order to cope with the growth and meet demand, researchers worldwide had to come up with new laser system. One of the areas of interest by is the development of the optical communication power source, i.e. the laser. Irrespective of whether it is a semiconductor laser or fibre laser, tremendous amount of research have been carried out to develop a better laser. There is a keen interest in developing a fibre laser. In this study we have develop a fibre laser system as the optical communication source. The fibre laser uses the standing wave or linear cavity configuration. It produces two output wavelengths tuneable within a 30nm region. The tuneability of these output wavelengths is independent of each other. The tuning was done while maintaining the output power level to be almost if not equal. The power difference between the output is restricted to less than 0.5dB The independent tuning and output power equality is achieved by controlling the system’s cavity loss. To do this, variable optical attenuators are placed inside the cavity. The attenuators will control the cavity loss, making it equal thus allowing the system to produce two output wavelengths simultaneously. The system has been characterised and the performance is comparable to other typical fibre laser system.